Economic and relationship-strengthening intervention to reduce alcohol use in couples living with HIV in Malawi: a study protocol for a randomised controlled trial of Mlambe - Torsten B Neilands; Lynae A Darbes; James Mkandawire; Derek S Brown; Fred M Ssewamala; Judith A Hahn; Amy A Conroy; Nancy Mulauzi; Scott Tebbetts (BMJ Open)
Introduction Heavy alcohol use has the potential to derail progress towards UNAIDS 95-95-95 targets for countries in sub-Saharan Africa (SSA). Within couples, alcohol use is closely linked with factors such as intimate partner violence and economic insecurity and can result in poor adherence to antiretroviral therapy (ART) and HIV clinical outcomes. We hypothesise that a combined economic and relationship intervention for couples that builds on the prior success of standalone economic and relationship-strengthening interventions will be efficacious for improving HIV clinical outcomes and reducing alcohol use. The synergy of these interventions has not been assessed in SSA—specifically among people living with HIV who drink alcohol. To test this hypothesis, we will test Mlambe, an economic and relationship-strengthening intervention, found to be feasible and acceptable in a pilot study in Malawi. We will conduct a full-scale, randomised controlled trial (RCT) to evaluate the efficacy and cost-effectiveness of Mlambe.Methods and analysis We will enrol 250 adult married couples having at least one partner living with HIV and reporting heavy alcohol use. There will be two arms: Mlambe or an enhanced usual care control arm. Couples in the Mlambe arm will receive incentivised matched savings accounts and monthly sessions on financial literacy, relationship skills, and alcohol reduction education and counselling. Participants will be assessed at baseline, 11 months, 15 months and 20 months to examine effects on heavy alcohol use, HIV viral suppression, ART adherence and couple relationship dynamics. Study hypotheses will be tested using multilevel regression models, considering time points and treatment arms. Programmatic costs will be ascertained throughout the study and incremental cost-effectiveness ratios will be computed for each arm.Ethics and dissemination The RCT has been approved by the University of California, San Francisco (UCSF) (Human Research Protection Program; Protocol Number 23-40642), and the study has been approved by the National Health Sciences Research Committee (NHSRC; Protocol Number 24/05/4431) in Malawi. Adverse events and remedial actions will be reported to authorities both in Malawi and at UCSF. Results will be disseminated to study participants, local health officials and HIV policy makers and through presentations at conferences and publications in peer-reviewed journals.Trial registration number ClinicalTrials.gov Protocol Registration; NCT06367348 registered on 19 April 2024; https://register.clinicaltrials.gov/. Protocol Version 1.0: 22 October 2024.